Studi Karakteristik Edible Film Dari Pektin Buah Pandan Laut (Pandanus ordorifer): Study of Edible Film Physicochemical Characteristics of Pandan Laut Fruit (Pandanus ordorifer) Pectin - Lubis, Novriyanti; Nuraeni, Ai Resna Fitri; Mahmudah, Rahma; Abdillah, Muhammad Nur; Prasetiawati, Riska (Universitas Bumigora, 2025)
Edible film is a thin layer used to protect food ingredients (as a coating) that comes from food-grade components and can be consumed directly. Pandanus sea fruit has the potential to be a source of pectin. This study aims to determine the characteristics of edible film from Pandanus sea fruit pectin (Pandanus ordorifer). The method used was laboratory experimental research with a simple one-factor experimental design. The pectin extraction formula consists of Pandanus sea simplicia, distilled water, and H2SO4, with variations in pH conditions at 2, 3, and 4. The results showed that pectin with pH 4 met the requirements according to the Japanese Industrial standard consisting of a yield of 2.60%, water content of 8.1%, ash content of 9.2%, methoxyl content of 6.2%, equivalent weight of 631 mg, galacturonic acid content of 253% and degree of esterification of 13.9%. The edible film making formula is Pandanus sea pectin, distilled water, with variations of sorbitol added at 5%, 10%, and 15%. The results showed that a concentration of 5% sorbitol produced the best edible film, meeting the requirements of a water content of 6.5%, a thickness of 0.13 mm, and a solubility of 59%. The organoleptic test of the edible film with a 5% sorbitol concentration was the most preferred by the panelists.This research is expected to be an innovation in the use of Pandan Laut fruit as an alternative food packaging.